Digital Marketing Strategy as a Promotional Effort Purwokerto Speciality Food CV. Eka Sari - Rafian Tri Akso; Fiby Nur Afiana; Gustin Setyaningsih (LPPM Universitas Potensi Utama, 2024)
In the context of digital marketing, which is increasingly important in the digital era, this research focuses on analyzing the digital promotion strategies implemented by CV. Eka Sari, a distributor of specialty food products in Purwokerto . The main objective is to evaluate the effectiveness of digital strategies in creating product differentiation and reaching a wider market. Using SWOT analysis method, business canvas model, and Porter's Five Forces, this research identifies the strengths, weaknesses, opportunities, and threats faced by CV. Eka Sari, as well as factors that affect competition in the market. The results show that CV. Eka Sari effectively utilizes digital marketing strategies, especially through social media, to strengthen brand awareness and attract the interest of the target market which includes students, productive employees, and families. Unique product differentiation and modern concepts have increased market share and strengthened their market position in the specialty food industry. The findings offer valuable insights for other specialty food product distributors in developing effective digital promotion strategies in the face of intensifying competition in the market.